Megapolis city region food systems and their vulnerability towards climate change related hazards - Thiel, Felix; Phillips, I.; Drechsel, Nikita (CGIAR Research Program on Water, Land and Ecosystems, 2020)
Urban growth in Sri Lanka’s Western Region Megapolis (WRM), home to 5.8 million people and projected to reach 9 million by 2030, has intensified pressure on city region food systems (CRFS). The WRM lacks sufficient arable land to support its population, making it reliant on surrounding districts for key staples like rice, coconut, fish, and vegetables. These city region’s food flows are increasingly vulnerable to climate change impacts. Droughts in the dry zone are expected to worsen, depleting water reserves and disrupting seasonal agricultural patterns. Between 1985 and 2004, over 1,400 drought events affected 8 million people and 280,000 hectares of crops. Floods and extreme rainfall events are becoming more frequent, causing crop failures and landslides in the wet zone, while extreme heat projected to rise by up to 2°C by 2060 threatens rice and coconut yields in high-producing regions. Sea level rise is also contributing to coastal erosion and saltwater intrusion, threatening groundwater supplies and low-lying farmland. To ensure future food security, city region food systems must be climate resilient. This requires spatial planning, hazard mapping, and adaptive agricultural strategies that account for changing rainfall, temperature, and sea-level conditions across climatic zones and food supply corridors.